Cataract surgery in Australia: a review of the regional literature and outcomes from 5018 cases at a tertiary teaching hospital - Chameen Samarawickrama; Muhammad A Khan; Brendon W H Lee; Lauren Sartor (BMJ Open Ophthalmology)
Objectives To report visual and surgical outcomes of phacoemulsification cataract surgery from 5018 consecutive cases from Sydney, Australia. A review of the Australian and New Zealand literature was undertaken to provide a benchmark of outcomes from the region.Methods The electronic medical record system was used to review three time-points for all phacoemulsification cataract surgeries at a tertiary-referral centre between May 2017 and August 2020: preoperative, intraoperative and one month postoperatively. Variables collected included uncorrected distance visual acuity (UDVA) and pinhole visual acuity, surgeon seniority and ocular pathology.Results Of the 5018 eyes, 37.3% were operated on by consultants, 47.1% by trainees and 15.6% by fellows. Ocular pathology was seen in 48.9% of eyes (n=1709). The mean preoperative and one month postoperative UDVA was 6/48 and 6/12, respectively. There was an intraoperative complication in 7.6% of eyes (n=379) and posterior capsular rupture (PCR) occurred in 2.7% (n=136). PCR rates between consultants (3.1%, n=56), trainees (2.6%, n=61) and fellows (2.1%, n=16) showed no statistically significant difference (p≥0.355). The key risk factors for PCR were advanced cataract, alpha-antagonist use, small pupil size and the presence of glaucoma.Conclusion We present visual and surgical outcomes from the largest study on phacoemulsification cataract surgery in Australia and New Zealand, acknowledging the study’s retrospective nature preventing inter-eye correlations, subdivision of cataract subspecialist versus not and trainee rank, and the minority of missing data. Our findings were comparable to regional and international benchmarks despite a high rate of ocular pathology and trainee case load. The lack of a regional cataract surgery registry represents a critical need in assessing and claiming key performance indicators, capturing emerging trends and identifying region-specific risk factors to deliver the best patient outcomes.